Associations between sexual sensation seeking and AIDS-related knowledge, attitudes and behaviors among young men who have sex with men in China. Issue 5 (28th May 2017) - Gao, Mengting; Xiao, Chenchang; Cao, Yue; Yu, Bin; Li, Shiyue; Yan, Hong
Abstract: Young men who have sex with men (YMSM) have become high risk groups for HIV infection in China. Recent researches suggest that sexual sensation seeking is significantly associated with AIDS-related knowledge, attitudes and behaviors, but the relationship is not clear in the field of YMSM in China. The present study aimed to evaluate the relationship between sexual sensation seeking and AIDS-related knowledge, attitudes, and behaviors among YMSM in China. A cross-sectional study was conducted in Wuhan, China from May to November 2013. 403 YMSM were recruited and 373 of them completed the questionnaire. Regression analyses indicated that YMSM with high sexual sensation seeking score are more likely to have low awareness of knowledge and negative attitude about condom use, as well as more risky sexual behaviors.